How Does Access to L1 Speech Affect L2 and L3 Perceived Fluency? - Lehtilä, Elina; Peltonen, Pauliina; Lintunen, Pekka (Scandinavian University Press / Universitetsforlaget AS, 2025)
While first language (L1) fluency and cross-linguistic influences have emerged as factors that contribute to second language (L2) speech fluency, the potential effects of L1 speaking style and cross-linguistic differences on target language (L2, L3…) perceived fluency remain largely unexplored. This study reports the results from two experiments that examined how access to speakers’ L1 Finnish speech influences the perceived fluency of L2 English (Experiment I) and L3 Swedish (Experiment II). L2 English and L3 Swedish speech elicited from the same L1 Finnish speakers (n = 20) were used in both experiments, and Experiment I also included L2 English speech samples from 10 Finnish–Swedish bilingual speakers to enable comparisons across different L1 backgrounds. Altogether 72 listeners participated in the two experiments and rated the speakers’ L2/L3 fluency either based solely on L2/L3 speech (control condition), or after listening to the speakers’ L1 Finnish speech (experimental condition). The results of Experiment I showed no significant effect of L1 background on perceived L2 English fluency, but the listeners with access to the speakers’ L1 speech assigned higher speed and repair fluency ratings for both speaker groups. In contrast, in Experiment II, the same L1 Finnish speakers received significantly lower ratings for all aspects of their L3 Swedish fluency by the listeners who had access to their L1 speech. The implications of the findings for fluency research, teaching, and assessment are discussed.